Pengaruh Aromaterapi Sebagai Relaksasi Dalam Mengurangi Stres Kerja Pada Pekerja Kantoran Dispendukcapil Surakarta - Nur Asri Yusuf; Reni Wijayanti; Tyas Lilia Wardani (Badan Riset dan Inovasi Daerah Kota Surakarta, 2024)
Work-related stress is one of the serious problems in the health sector in Indonesia. Based on the results of the Mercer Marsh Benefit 2021 survey involving more than 1,000 workers in Indonesia, it was found that 40% of workers experienced stress due to work. This situation illustrates that workers in Indonesia are vulnerable to psychological problems or emotional disorders. The demands of the task, the many procedures that must be followed and the demands for quality service to the community are one of the causes of stress in workers. Formal workers who are vulnerable to job stress are government employees. This study aims to determine the effect of aromatherapy as relaxation in reducing work stress in office workers at Dispendukcapil Surakarta. This study uses a pre-experimental design research method using a one group pretest posttest design. Respondents were taken from Dispendukcapil office workers totalling 41 respondents out of a total of 79 workers. The sampling technique used was nonprobability sampling with purposive sampling method. This study use handkerchiefs and Aromatherapy lavender and roses and questionnaires measure the level of work stress. The data analysis technique used is the Wilcoxon test. The results showed 25 respondents experienced a decrease in work stress. The results of statistical tests between pretest and posttest results using the Wilcoxon test showed a p value of 0.000 (p 0.05), this indicates a significant effect of giving aromatherapy on reducing the work stress of respondents.